Independent factors associated with wearing different types of outdoor footwear in a representative inpatient population: a cross-sectional study - Alex L. Barwick; Jaap J. van Netten; Lloyd F. Reed; Peter A. Lazzarini (Journal of Foot and Ankle Research, 2018)
Abstract Background Footwear can have both a positive and negative impact on lower limb health and mobility across the lifespan, influencing the risk of foot pain, ulceration, and falls in those at risk. Choice of footwear can be influenced by disease as well as sociocultural factors, yet few studies have investigated the types of footwear people wear and the profiles of those who wear them. The aim of this study was to investigate the prevalence and factors associated with outdoor footwear type worn most often in a representative inpatient population. Methods This study was a secondary data analysis of a cohort of 733 inpatients that is highly representative of developed nations’ hospitalised populations; 62 ± 19 years, 55.8% male, and 23.5% diabetes. Socio-demographic, medical history, peripheral arterial disease, peripheral neuropathy, foot deformity, foot ulcer history, amputation history and past foot treatment variables were collected. Participants selected the footwear type they mostly wore outside the house in the previous year from 16 types of footwear. Multivariate logistic regression identified independent factors associated with outdoor footwear types selected. Results The most common outdoor footwear types were: running shoes (20%), thongs/flip flops (14%), walking shoes (14%), sandals (13%) and boots (11%). Several socio-demographic, medical history and foot-related factors were independently associated (Odds Ratio; 95% Confidence Interval)) with different types of footwear. Running shoes were associated with male sex (2.7; 1.8–4.1); thongs with younger age (0.95 for each year; 0.94–0.97), being female (2.0; 1.2–3.1) and socio-economic status (3.1; 1.2–7.6); walking shoes with arthritis (1.9; 1.2–3.0); sandals with female sex (3.8; 2.3–6.2); boots with male sex (9.7; 4.3–21.6) and inner regional (2.6; 1.3–5.1) and remote (3.4; 1.2–9.5) residence (all, p < 0.05). Conclusions We profiled the types of outdoor footwear worn most in a large diverse inpatient population and the factors associated with wearing them. Sex was the most consistent factor associated with outdoor footwear type. Females were more likely to wear thongs and sandals and males boots and running shoes. Overall, this data gives insights into the socio-demographic, medical and other health factors that are related to footwear choice in a large diverse population primarily of older age.